Exact impact response of multi-layered cement-based piezoelectric composite considering electrode effect. (February 2019) - Zhang, Taotao; Zhang, Keping; Liu, Wende
Multi-layered cement-based piezoelectric composites could enable accurate real-time detection of the concrete structure deformation induced by impact load. An analytical method for quantifying the impact response of the multi-layered cement-based piezoelectric composite is established based on the piezo-elasticity, and a general transfer matrix description for the composite with any number of layers is derived. The motion of the composite is decomposed into natural modes according to its physical significance of vibration modes. The mechanical and electrical solutions are obtained via the mode summation method and the virtual work principle. In order to give a clear demonstration, some numerical simulations are conducted to verify the validity of the theoretical analysis. Moreover, the current analytical method considers the electrode as an extra layer and evaluates the effect of its thickness and material on the performance of the multi-layered cement-based piezoelectric composite. It can be seen that the mathematical model presented in this article provides a rigorous tool for the analysis of the multi-layered cement-based piezoelectric composite and therefore could benefit the design of certain types of smart devices under impact load.